Oat bran in cardiovascular risk control in mental disorder - Elen Cristiane Doná Oliveira; Guilherme Correa Barbosa; José Eduardo Corrente; Jéssica Emy Komuro; Silvia Justina Papini
ABSTRACT Objective: To evaluate the effect of oat bran supplementation on cardiovascular risk components of patients with mental disorders. Method: A before-and-after study, no control group. Cardiovascular risk indicators were assessed at baseline (M0), 90 (M1), 180 days (M2) and 180 days after supplementation (M3). Results: Of the 45 patients admitted to a psychiatric institution using antipsychotics, more than two thirds had high cardiovascular risk assessed by abdominal obesity. Forty-six point seven percent were overweight and 31.1% metabolic syndrome. Oat bran was effective in reducing serum cholesterol (M0-M1), HDL-cholesterol (M1-M2), triglycerides (M1-M2), (M2-M3) and (M1-M3). In M3, there was a statistical difference for all indicators evaluated. Conclusion: Oat bran supplementation was effective in improving triglyceride, total cholesterol and HDL-cholesterol levels, suggesting that it is a therapeutic option for cardiovascular risk control in patients with psychiatric disorders.